Preparation method of double-side coated positive pole piece and solid-state battery

By adopting a double-sided coating preparation method on the positive electrode sheet of the solid-state battery, the problem of welding or adhesion of the electrode sheet between the single-sided coated electrode sheets is solved, which simplifies operation and improves the energy density and cycling performance of the battery.

CN119447188APending Publication Date: 2025-02-14GTC-POWER ZHUHAI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411424539.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, welding or adhesion of the electrode ears is required between single-sided coated electrode sheets, resulting in steps close to the electrode ears between the current collectors may affect the battery circulation performance and the operation content is cumbersome.

Method used

The preparation method of double-sided coated positive electrode sheet is adopted. The positive electrode slurry is made by mixing the positive electrode active substance, solid electrolyte, and conductive agent and stirring it with glue and solvent. The positive electrode slurry is coated on both sides of the current collector using a scraper and an adjustable scraper. The mixture was coated and vacuum dried to obtain a double-sided coated positive electrode sheet.

Benefits of technology

This method simplifies the coating operation, avoids the bonding steps between multiple current collectors, ensures the flatness and thickness consistency of the positive electrode sheet, maximizes the utilization rate of the positive electrode slurry, and improves the energy density and circulation of the battery. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081787630000081
    Figure BDA0005081787630000081
Patent Text Reader

Abstract

The invention discloses a preparation method of a double-side coated positive pole piece and a solid-state battery, and belongs to the technical field of solid-state batteries. A positive active material, a solid electrolyte and a conductive agent are taken as raw materials, a glue solution and a solvent are added and stirred to prepare positive slurry, and the positive slurry is coated on two sides of a current collector and is subjected to vacuum drying to prepare the double-side coated positive pole piece. The invention also provides a solid battery which is prepared by laminating the double-sided coated positive pole piece prepared by the method, an electrolyte pole piece and a negative pole piece. According to the invention, the operation content of double-sided coating of the positive pole piece is simplified, the step of combining multiple current collectors is avoided, the thickness of the double-sided coating layer of the positive pole piece can be controlled, the utilization rate of the positive pole slurry is improved to the maximum extent, and the energy density of the battery is improved; steps existing between the two positive electrodes during single-side coating are eliminated, the problems of unevenness of positive electrode planes and breakage of current collectors are avoided, and comprehensive and good contact of positive electrode / electrolyte interfaces is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and specifically relates to a method for preparing a double-sided coated positive electrode plate and a solid-state battery. Background Art

[0002] When traditional liquid lithium-ion batteries are used in pure electric vehicles, liquid electrolyte leakage after accidents such as collisions can easily cause fires and explosions. Solid-state batteries use solid electrolytes instead of liquid electrolytes to improve safety performance and avoid leakage and combustion after collisions. In addition, they can also increase the range of electric vehicles and shorten charging time. They are the next generation of batteries with great potential.

[0003] Solid-state battery electrodes can be prepared by dry rolling or wet coating. The wet coating method currently has high preparation efficiency, high electrode flatness, good thickness consistency, and is easier to prepare in batches. After drying, it can be used to prepare solid-state batteries. In the existing preparation methods of double-layer and multi-layer solid-state batteries, there are general single-sided coated electrode plates that need to be welded or adhered to the pole ears. The steps between the current collectors near the pole ears may affect the battery cycle performance, and there are also relatively cumbersome technical issues in the operation content. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a double-sided coated positive electrode plate and a solid-state battery, which are used to solve the technical problems in the prior art that generally single-sided coated electrode plates need to be welded or adhered to the pole ears, the steps between the current collectors near the pole ears may affect the battery cycle performance, and the operation content is also relatively cumbersome.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a double-sided coated positive electrode sheet comprises the following steps:

[0007] S1, mixing the positive electrode active material, the solid electrolyte and the conductive agent and stirring to obtain a positive electrode mixture;

[0008] S2, mixing a binder and a solvent A to form a glue solution, adding the glue solution to the positive electrode mixture, adding the solvent A to adjust the solid content, and performing shear stirring to obtain a positive electrode slurry;

[0009] S3. Use a scraper of specified specifications to coat the positive electrode slurry on one side of the current collector, and after drying, use an adjustable scraper to coat the other side. After vacuum drying, a double-sided coated positive electrode sheet is obtained.

[0010] Preferably, the positive electrode active material in S1 includes any combination of one or more of lithium cobalt oxide, lithium iron phosphate, layered lithium manganese oxide, and nickel cobalt lithium manganese oxide.

[0011] Preferably, the solid electrolyte in S1 includes any combination of one or more of lithium phosphorus sulfur chlorine, lithium germanium phosphorus sulfur, and lithium phosphorus sulfur.

[0012] Preferably, the conductive agent in S1 includes any combination of one or more of graphite, carbon nanotubes, carbon black, graphene, and carbon fiber.

[0013] Preferably, the mass ratio of the positive electrode active material, the solid electrolyte and the conductive agent in S1 is 60-80:10-40:1-5, and preferably, the mass ratio of the positive electrode active material, the solid electrolyte and the conductive agent is 70:28:2.

[0014] Preferably, the stirring method in S1 is dry mixing stirring, the stirring speed is 10000-20000 rpm, stirring is 8 times for 30 seconds each time, each stirring interval is 2 minutes, and the whole operation is carried out in an argon-filled glove box.

[0015] Preferably, the binder in S2 includes any combination of one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-ethylene-butadiene-styrene block copolymer, polyacrylic acid, and polyisobutylene.

[0016] Preferably, the solvent A in S2 includes any combination of one or more of toluene, p-xylene, N-methylpyrrolidone, n-heptane, n-hexane, tetrahydrofuran, and cyclohexane, and the solid content of the glue is 0.5-10%, preferably, the solid content of the glue is 5%.

[0017] Preferably, the mass ratio of the positive electrode mixture to the binder in S2 is 97-99.5:10-30, and preferably the mass ratio of the positive electrode mixture to the binder is 99:20.

[0018] Preferably, a degassing mixer is used in S2 for shear stirring, and the shear stirring needs to be performed multiple times. The stirring interval depends on the heating situation. Stirring is performed after complete cooling. The stirring speed is 300 to 2000 rpm, and each stirring time is 2 to 8 minutes. After the stirring is completed, the positive electrode slurry obtained has a certain fluidity and no obvious particles.

[0019] Preferably, the solid content of the positive electrode slurry in S2 is 70-80%. Preferably, the solid content of the positive electrode slurry is 75%.

[0020] Preferably, the current collector in S3 is an aluminum foil coated with carbon on both sides.

[0021] Preferably, the fixed specification of the scraper in S3 is 200 μm. After coating, it is placed on a 60°C flat hot table for drying. After the solvent on the electrode surface evaporates, the electrode thickness δ is measured. The thickness of the positive electrode coating layer after drying is 50 to 200 μm.

[0022] Preferably, an adjustable scraper is used for coating the other side in S3, and the adjustment specification is 200 μm+δ.

[0023] Preferably, after the double-sided coating in S3 is completed, the double-sided coated positive electrode sheet is placed in a vacuum oven at 60° C. and vacuum dried for 12 to 18 hours to prepare the double-sided coated positive electrode sheet.

[0024] The present invention also provides a solid battery, comprising an electrolyte, a negative electrode and a double-sided coated positive electrode plate prepared by the above method.

[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0026] 1. The present invention uses positive electrode active material, solid electrolyte, and conductive agent as raw materials, adds glue and solvent, and stirs to form positive electrode slurry. The positive electrode slurry is coated on both sides of the current collector using a scraper and an adjustable scraper, and then vacuum dried to prepare a double-sided coated positive electrode sheet. Using a scraper and an adjustable scraper to coat the positive electrode simplifies the coating operation and avoids the step of combining multiple current collectors. The controllable thickness of the double-sided coating layer of the positive electrode sheet allows the front and back of the current collector to be in a free penetration state, which maximizes the utilization rate of the positive electrode slurry, thereby improving the energy density of the battery.

[0027] 2. The double-sided coated positive electrode plate provided by the present invention eliminates the step between the two positive electrodes during single-sided coating in the preparation of double-layer or multi-layer solid-state batteries, avoids the problems of uneven positive electrode plane and collector breakage, maintains comprehensive and good contact of the positive electrode / electrolyte interface, and the controllable thickness of the double-sided coating layer of the positive electrode plate maximizes the utilization rate of the positive electrode slurry, so that the front and back sides of the collector are in a free penetration state, thereby improving the energy density of the battery.

[0028] 3. The solid battery provided by the present invention has better initial efficiency and cycle performance than the traditional battery with a single-sided coated electrode. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1: A method for preparing a double-sided coated positive electrode sheet of this embodiment comprises the following steps:

[0031] S1. In an argon-filled glove box, lithium nickel cobalt manganese oxide, lithium phosphorus sulfur chlorine electrolyte and vapor-deposited carbon fiber were weighed in a mass ratio of 70:28:2, mixed and dry-mixed at a speed of 12000 rpm for 8 times for 30 seconds each, with an interval of 2 minutes between each stirring, to obtain a positive electrode mixture;

[0032] S2. Mix polyvinylidene fluoride and N-methylpyrrolidone in a mass ratio of 5:95 to prepare a glue with a solid content of 5%, weigh the positive electrode mixture and the glue in a mass ratio of 99:20, add N-methylpyrrolidone to adjust the solid content to 75%, use a deaerator to shear and stir, stir at 300 rpm for 3 min, stir at 800 rpm for 3 min, stir at 1500 rpm for 3 min, and stir 3 times to obtain a positive electrode slurry;

[0033] S3. Use a 200 μm scraper to coat the positive electrode slurry on one side of the current collector, place it on a 60°C flat hot plate to dry, measure the electrode thickness δ after the surface solvent evaporates, and use an adjustable scraper adjusted to (δ+200) μm to coat the other side after drying. After vacuum drying for 12 hours, a double-sided coated positive electrode electrode is obtained.

[0034] The preparation method of the solid battery of this embodiment is as follows: the dried double-sided coated positive electrode plate, the lithium phosphorus sulfur chlorine electrolyte plate and the graphite negative electrode plate are laminated and pressed to obtain a double-layer solid-state battery.

[0035] Embodiment 2, a method for preparing a double-sided coated positive electrode sheet of this embodiment comprises the following steps:

[0036] S1. In an argon-filled glove box, lithium nickel cobalt manganese oxide, lithium phosphorus sulfur chlorine electrolyte and vapor-deposited carbon fiber were weighed in a mass ratio of 60:38:2, mixed and dry-mixed at a speed of 10000 rpm for 8 times for 30 seconds each, with an interval of 2 minutes between each stirring, to obtain a positive electrode mixture;

[0037] S2. Mix polyvinylidene fluoride and N-methylpyrrolidone in a mass ratio of 5:95 to prepare a glue with a solid content of 5%, weigh the positive electrode mixture and the glue in a mass ratio of 99.5:10, add N-methylpyrrolidone to adjust the solid content to 70%, use a deaerator to shear and stir, stir at 300 rpm for 2 min, stir at 800 rpm for 2 min, stir at 1500 rpm for 2 min for 3 times, and obtain a positive electrode slurry;

[0038] S3. Use a 200 μm scraper to coat the positive electrode slurry on one side of the current collector, place it on a 60°C flat hot plate to dry, measure the electrode thickness δ after the surface solvent evaporates, and use an adjustable scraper adjusted to (δ+200) μm to coat the other side after drying. After vacuum drying for 12 hours, a double-sided coated positive electrode electrode is obtained.

[0039] The preparation method of the solid battery of this embodiment is as follows: the dried double-sided coated positive electrode plate, the lithium phosphorus sulfur chlorine electrolyte plate and the graphite negative electrode plate are laminated and pressed to obtain a double-layer solid-state battery.

[0040] Embodiment 3, a method for preparing a double-sided coated positive electrode sheet of this embodiment comprises the following steps:

[0041] S1. In an argon-filled glove box, lithium nickel cobalt manganese oxide, lithium phosphorus sulfur chlorine electrolyte and vapor-deposited carbon fiber were weighed in a mass ratio of 80:18:2, mixed and dry-mixed at a speed of 20,000 rpm for 8 times for 30 seconds each, with an interval of 2 minutes between each stirring, to obtain a positive electrode mixture;

[0042] S2. Mix polyvinylidene fluoride and N-methylpyrrolidone in a mass ratio of 5:95 to prepare a glue with a solid content of 5%, weigh the positive electrode mixture and the glue in a mass ratio of 99:20, add N-methylpyrrolidone to adjust the solid content to 80%, use a deaerator to shear and stir, stir at 300 rpm for 8 min, stir at 800 rpm for 8 min, stir at 1500 rpm for 8 min for 3 times, and obtain a positive electrode slurry;

[0043] S3. Use a 200 μm scraper to coat the positive electrode slurry on one side of the current collector, place it on a 60°C flat hot plate to dry, measure the electrode thickness δ after the surface solvent evaporates, and use an adjustable scraper adjusted to (δ+200) μm to coat the other side after drying. After vacuum drying for 18 hours, a double-sided coated positive electrode electrode is obtained.

[0044] The preparation method of the solid battery of this embodiment is as follows: the dried double-sided coated positive electrode plate, the lithium phosphorus sulfur chlorine electrolyte plate and the graphite negative electrode plate are laminated and pressed to obtain a double-layer solid-state battery.

[0045] Embodiment 4, a method for preparing a double-sided coated positive electrode plate of this embodiment comprises the following steps:

[0046] S1. In an argon-filled glove box, lithium nickel cobalt manganese oxide, lithium phosphorus sulfur chlorine electrolyte and vapor-deposited carbon fiber were weighed in a mass ratio of 80:15:5, mixed and dry-mixed at a speed of 15000 rpm for 8 times for 30 s each, with an interval of 2 min between each stirring, to obtain a positive electrode mixture;

[0047] S2. Mix polyvinylidene fluoride and N-methylpyrrolidone in a mass ratio of 2:98 to prepare a glue with a solid content of 2%, weigh the positive electrode mixture and the glue in a mass ratio of 99.5:25, add N-methylpyrrolidone to adjust the solid content to 70%, use a deaerator to shear and stir, stir at 300 rpm for 3 min, stir at 800 rpm for 3 min, stir at 1500 rpm for 3 min, and stir 3 times to obtain a positive electrode slurry;

[0048] S3. Use a 200 μm scraper to coat the positive electrode slurry on one side of the current collector, place it on a 60°C flat hot plate to dry, measure the electrode thickness δ after the surface solvent evaporates, and use an adjustable scraper adjusted to (δ+200) μm to coat the other side after drying. After vacuum drying for 16 hours, a double-sided coated positive electrode electrode is obtained.

[0049] The preparation method of the solid battery of this embodiment is as follows: the dried double-sided coated positive electrode plate, the lithium phosphorus sulfur chlorine electrolyte plate and the graphite negative electrode plate are laminated and pressed to obtain a double-layer solid-state battery.

[0050] Embodiment 5, a method for preparing a double-sided coated positive electrode sheet of this embodiment comprises the following steps:

[0051] S1. In an argon-filled glove box, lithium nickel cobalt manganese oxide, lithium phosphorus sulfur chlorine electrolyte and vapor-deposited carbon fiber were weighed in a mass ratio of 75:20:5, mixed and dry-mixed at a speed of 12000 rpm for 8 times for 30 seconds each, with an interval of 2 minutes between each stirring, to obtain a positive electrode mixture;

[0052] S2. Mix polyvinylidene fluoride and N-methylpyrrolidone in a mass ratio of 10:90 to prepare a glue with a solid content of 10%, weigh the positive electrode mixture and the glue in a mass ratio of 97:30, add N-methylpyrrolidone to adjust the solid content to 75%, use a deaerator to shear and stir, stir at 300 rpm for 3 min, stir at 800 rpm for 3 min, stir at 1500 rpm for 3 min, and stir 3 times to obtain a positive electrode slurry;

[0053] S3. Use a 200 μm scraper to coat the positive electrode slurry on one side of the current collector, place it on a 60°C flat hot plate to dry, measure the electrode thickness δ after the surface solvent evaporates, and use an adjustable scraper adjusted to (δ+200) μm to coat the other side after drying. After vacuum drying for 14 hours, a double-sided coated positive electrode electrode is obtained.

[0054] The preparation method of the solid battery of this embodiment is as follows: the dried double-sided coated positive electrode plate, the lithium phosphorus sulfur chlorine electrolyte plate and the graphite negative electrode plate are laminated and pressed to obtain a double-layer solid-state battery.

[0055] Embodiment 6, a method for preparing a double-sided coated positive electrode sheet of this embodiment comprises the following steps:

[0056] S1. In an argon-filled glove box, lithium nickel cobalt manganese oxide, lithium phosphorus sulfur chlorine electrolyte and vapor-deposited carbon fiber were weighed in a mass ratio of 75:22:3, mixed and dry-mixed at a speed of 19000 rpm for 8 times for 30 s each, with an interval of 2 min between each stirring, to obtain a positive electrode mixture;

[0057] S2. Mix polyvinylidene fluoride and N-methylpyrrolidone to prepare a glue with a solid content of 5%, weigh the positive electrode mixture and the glue in a mass ratio of 99:20, add N-methylpyrrolidone to adjust the solid content to 80%, use a deaerator to shear and stir, stir at 300 rpm for 3 min, stir at 800 rpm for 3 min, stir at 1500 rpm for 3 min, and stir 3 times to obtain a positive electrode slurry;

[0058] S3. Use a 200 μm scraper to coat the positive electrode slurry on one side of the current collector, place it on a 60°C flat hot plate to dry, measure the electrode thickness δ after the surface solvent evaporates, and use an adjustable scraper adjusted to (δ+200) μm to coat the other side after drying. After vacuum drying for 15 hours, a double-sided coated positive electrode electrode is obtained.

[0059] The preparation method of the solid battery of this embodiment is as follows: the dried double-sided coated positive electrode plate, the lithium phosphorus sulfur chlorine electrolyte plate and the graphite negative electrode plate are laminated and pressed to obtain a double-layer solid-state battery.

[0060] Comparative Example 1: The difference between this comparative example and Example 1 is that the preparation method of the positive electrode plate is changed to use a 200 μm scraper to evenly apply the slurry to one side of the carbon-coated aluminum foil, and the two dried single-sided coated positive electrode plates are bonded to the pole ears with conductive glue.

[0061] Test Example 1: The solid-state battery prepared in the embodiment and the solid-state battery prepared in the comparative example were subjected to performance tests respectively. The results are shown in Table 1.

[0062] Table 1. Battery performance of solid-state batteries of the embodiment and solid-state batteries of the comparative example

[0063]

[0064] As can be seen from Table 1, compared with the solid-state battery in Comparative Example 1, the solid-state batteries in Examples 1 to 6 have higher first coulombic efficiency, first-week discharge capacity, and 200-week capacity retention rate than the solid-state battery in Comparative Example 1, and the first efficiency is above 80%, indicating that the electrochemical performance of the positive electrode of the solid-state battery prepared by the preparation method in Examples 1 to 6 of the present application is better. The first-week discharge capacity is above 172mAh / g, and the 200-week capacity retention rate is above 83%, indicating that the double-sided coated positive electrode sheet prepared in Examples 1 to 6 of the present application reduces the loss of battery cycle discharge capacity, further indicating that the preparation method in the embodiment of the present application optimizes the battery structure and achieves the optimization of cycle performance.

[0065] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0066] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a double-sided coated positive electrode sheet, characterized in that: The steps include: S1, mixing the positive electrode active material, the solid electrolyte and the conductive agent and stirring to obtain a positive electrode mixture; S2, mixing a binder and a solvent A to form a glue solution, adding the glue solution to the positive electrode mixture, and then adding the solvent A to adjust the solid content, and performing shear stirring to obtain a positive electrode slurry; S3. Use a scraper to coat the positive electrode slurry on one side of the current collector, and after drying, use an adjustable scraper to coat the other side. After vacuum drying, a double-sided coated positive electrode sheet is obtained.

2. The method for preparing a double-sided coated positive electrode sheet according to claim 1, characterized in that: The positive electrode active material in S1 includes any combination of one or more of lithium cobalt oxide, lithium iron phosphate, layered lithium manganese oxide, and nickel cobalt manganese oxide; the solid electrolyte includes any combination of one or more of lithium phosphorus sulfur chlorine, lithium germanium phosphorus sulfur, and lithium phosphorus sulfur; and the conductive agent includes any combination of one or more of graphite, carbon nanotubes, carbon black, graphene, and carbon fiber.

3. The method for preparing a double-sided coated positive electrode sheet according to claim 1, characterized in that: The mass ratio of the positive electrode active material, the solid electrolyte and the conductive agent in the S1 is 60-80:10-40:1-5.

4. The method for preparing a double-sided coated positive electrode sheet according to claim 1, characterized in that: The stirring method in S1 is dry mixing stirring, the stirring speed is 10000-20000 rpm, stirring is 8 times, each time for 30 seconds, and the interval between each stirring is 2 minutes.

5. The method for preparing a double-sided coated positive electrode sheet according to claim 1, characterized in that: The binder in S2 includes any combination of one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-ethylene-butadiene-styrene block copolymer, polyacrylic acid, and polyisobutylene; the solvent A includes any combination of one or more of toluene, p-xylene, N-methylpyrrolidone, n-heptane, n-hexane, tetrahydrofuran, and cyclohexane; and the solid content of the glue is 0.5 to 10%.

6. The method for preparing a double-sided coated positive electrode sheet according to claim 1, characterized in that: In the S2, a degassing mixer is used for shear stirring, and stirring is performed again after cooling completely. The stirring speed is 300 to 2000 rpm, and the stirring time is 2 to 8 minutes each time. The solid content of the positive electrode slurry is 70 to 80%.

7. The method for preparing a double-sided coated positive electrode sheet according to claim 1, characterized in that: The current collector in S3 is a double-sided carbon-coated aluminum foil, and the fixed specification of the scraper is 200μm. After coating, it is placed on a 60°C flat hot table for drying. After the solvent on the surface of the pole piece evaporates, the pole piece thickness δ is measured. The thickness of the positive electrode coating layer after drying is 50-200μm. An adjustable scraper is used for coating on the other side, and the adjustment specification is 200μm+δ. After double-sided coating is completed, it is placed in a 60°C vacuum oven for vacuum drying for 12-18h.

8. A solid-state battery, characterized in that: The double-sided coated positive electrode sheet prepared according to any one of claims 1 to 7 is pressed together with the electrolyte electrode sheet and the negative electrode sheet.